A simple and highly sensitive elisa for screening of the α-thalassemia-1 southeast asian-type deletion - Pata S. (2014)
Couples in which both partners carry the α-thalassemia-1 trait have a 25% risk of hemoglobin Bart's hydrops fetalis in each pregnancy. Identification of α-thalassemia-1 trait is, therefore, necessary in order to control this severe form of α-thalassemia. We have generated monoclonal antibodies specific to the ζ-globin chain without cross reaction with other globin chains. A simple and sensitive ELISA was developed by using poly-l-lysine to increase the protein binding to the ELISA plate. The developed poly-l-lysine pre-coated ELISA has a very high sensitivity (100%) and specificity (97%) for detection of carriers of α-thalassemia-1 with Southeast Asian-type deletion. © 2014 Copyright Taylor and Francis Group, LLC.